2016
DOI: 10.1007/s10856-016-5703-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-responsive methylcellulose hydrogels as temporary substrate for cell sheet biofabrication

Abstract: Methylcellulose (MC), a water-soluble polymer derived from cellulose, was investigated as a possible temporary substrate having thermo-responsive properties favorable for cell culturing. MC-based hydrogels were prepared by a dispersion technique, mixing MC powder (2, 4, 6, 8, 10, 12 % w/v) with selected salts (sodium sulphate, Na2SO4), sodium phosphate, calcium chloride, or phosphate buffered saline, to evaluate the influence of different compositions on the thermo-responsive behavior. The inversion test was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 39 publications
2
65
0
Order By: Relevance
“…These data are in accordance to previous literature showing the lack of MC toxicity20212223242526 and thus its suitability as dedicated material for tissue engineering purposes. Moreover, according to in vitro 28 and here presented in vivo results, it can be concluded that the use of Na 2 SO 4 salt in combination with MC does not lead to any inflammatory reaction.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…These data are in accordance to previous literature showing the lack of MC toxicity20212223242526 and thus its suitability as dedicated material for tissue engineering purposes. Moreover, according to in vitro 28 and here presented in vivo results, it can be concluded that the use of Na 2 SO 4 salt in combination with MC does not lead to any inflammatory reaction.…”
Section: Resultssupporting
confidence: 69%
“…2B and C). The physical gelation of MC hydrogels was visually observed using the inversion method already described in the literature2628. The measurements showed that the gelation temperature of the selected MC hydrogel occurs between 34 and 37 °C, allowing us to handle cell constructs for some minutes without losing stability as previously shown28.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Herein, HEC, which is a kind of non-ionic cellulose ether with good water solubility and can be easily manufactured using natural cellulose as a raw material, is used as the hydrogel matrix, instead of synthetic polymers, taking advantage of cellulose resources, including its renewable nature, biocompatibility and biodegradability. [33][34][35] To our knowledge, no studies have been performed on the formation of self-assembled supramolecular hydrogels between hydrophobically modied HEC and b-CDP.…”
Section: 26-29mentioning
confidence: 99%
“…[41][42][43][44] First, 10 g of b-CD was dissolved in 15 mL of 15 wt% NaOH by stirring overnight at room temperature. Then the mixture was heated to 35 C and 7 mL of EPI was added in a 1 : 10 b-CD : EPI molar ratio. Aer 200 min, the mixture was poured into a dialysis bag (MWCO 8-12 kDa, Biosharp, USA) and dialyzed for 7 days.…”
Section: Preparation Of B-cdpmentioning
confidence: 99%